INDIVIDUAL ASPECTS OF CLINICAL AND PARACLINICAL EVALUATION OF PATIENTS WITH RESTORATIVE THERAPY BASED ON METAL-COMPOSITE CONSTRUCTION - Daniela-Mariana Calamaz; Marcel Costuleanu; Norina Consuela Forna (Romanian Society of Oral Rehabilitation, 2017)
The explosion of a large number of materials introduced into restorative practice variable composition, often puts us in difficulty in choosing those with the best possible quality. This is because each class of materials requires a certain technology for processing and finishing, which, if not met, could compromise the benefits and performance of the material.The study looked at the impact of different types of composite restorations to come into contact with the marginal periodontium, in full agreement with the types of biomaterials involved in triggering or perpetuating periodontal pathology.The study group included 121 patients in the Clinical Education Base of the Faculty of Dental Medicine Iaşi, having been diagnosed with different types of edentation and who benefited and will benefit of various composite restorative techniques.The therapeutic variants in the treated cases with prosthetic restorations with mixed materials made of metal-acrylic alloy and acrylic Verasoft not always complying the sulcular gingival contour or the biological width in placing the edges, with negative effects of periodontal involvement is a common clinical reality in a statistically significant number of cases.The results of clinical and laboratory evaluation of analyzed patients provide a clear image of the need for the performance of future correlative studies established between the patient's general condition, the type of composite restoration, the type of preparation and the effects on the physiology and pathophysiology of periodontal.